Brain endothelial cell-derived extracellular vesicles with a mitochondria-targeting photosensitizer effectively treat glioblastoma by hijacking the blood‒brain barrier - Thuy Giang Nguyen Cao; Ji Hee Kang; Su Jin Kang; Quan Truong Hoang; Han Chang Kang; Won Jong Rhee; Yu Shrike Zhang; Young Tag Ko; Min Suk Shim (Elsevier, 2023)
Glioblastoma (GBM) is the most aggressive malignant brain tumor and has a high mortality rate. Photodynamic therapy (PDT) has emerged as a promising approach for the treatment of malignant brain tumors. However, the use of PDT for the treatment of GBM has been limited by its low blood‒brain barrier (BBB) permeability and lack of cancer-targeting ability. Herein, brain endothelial cell-derived extracellular vesicles (bEVs) were used as a biocompatible nanoplatform to transport photosensitizers into brain tumors across the BBB. To enhance PDT efficacy, the photosensitizer chlorin e6 (Ce6) was linked to mitochondria-targeting triphenylphosphonium (TPP) and entrapped into bEVs. TPP-conjugated Ce6 (TPP-Ce6) selectively accumulated in the mitochondria, which rendered brain tumor cells more susceptible to reactive oxygen species-induced apoptosis under light irradiation. Moreover, the encapsulation of TPP-Ce6 into bEVs markedly improved the aqueous stability and cellular internalization of TPP-Ce6, leading to significantly enhanced PDT efficacy in U87MG GBM cells. An in vivo biodistribution study using orthotopic GBM-xenografted mice showed that bEVs containing TPP-Ce6 [bEV(TPP-Ce6)] substantially accumulated in brain tumors after BBB penetration via transferrin receptor-mediated transcytosis. As such, bEV(TPP-Ce6)-mediated PDT considerably inhibited the growth of GBM without causing adverse systemic toxicity, suggesting that mitochondria are an effective target for photodynamic GBM therapy.